Determining dynamic characteristics of high rise buildings using interferometric radar system. (1st June 2018) - Sofi, M.; Lumantarna, E.; Zhong, A.; Mendis, P.A.; Duffield, C.; Barnes, R.
Highlights: Non-contact interferometric radar system (IBIS-FS) is used to capture the dynamic characteristics of two high rise buildings. Field measurements are compared with finite element analysis of the high rise buildings. Mode shapes from the surveyed displacement time histories are extracted. Abstract: Dynamic performance measurement of buildings using conventional contact sensors such as accelerometers, tilt meters and Global Positioning System (GPS) can be difficult due to accessibility restrictions, particularly during construction or retrofitting periods. This is one of the first studies using a non-contact microwave interferometry radar based system for dynamic measurement of high rise buildings. This paper presents results of a combined experimental and analytical approach to investigate modal properties of two high rise buildings in Australia. Dynamic properties of the buildings, namely Soul building and Zen Apartments, were investigated. The choices of the buildings were based on the different physical properties and plan layouts of the buildings. To capture the dynamic characteristics of the buildings, field measurements were carried out using an interferometric radar based equipment and compared with results from more conventional contact-sensors such as accelerometers and GPS. The building vibration test results were then correlated with the buildings' respective finite element modelling (FEM) simulations to test the capability of the radar in capturing mode shapes of the buildings. Finite elements software ETABS was used for this purpose. Results show that interferometric radar system has the potential as a non-contact instrument to be effectively used to measure the dynamic properties including mode shapes of high rise buildings.